2011 International Joint Conference on Biometrics (IJCB) 2011
DOI: 10.1109/ijcb.2011.6117476
|View full text |Cite
|
Sign up to set email alerts
|

Facial recognition of identical twins

Abstract: Biometric identification systems must be able to distin guish between individuals even in situations where the bio metric signature may be similar, such as in the case of iden tical twins. This paper presents experiments done in facial recognition using data from a set of images of twins. This work establishes the current state of facial recognition in regards to twins and the accuracy of current state-of-the art programs in distinguishing between identical twins us ing three commercial face matchers, Cognitec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…However, experiments conducted by Daugman and Downing in 5 [2], by Jain et al in [3], by Srihari et al in [4], and by Kong et al in [5] have shown that biometric identifiers such as the iris, fingerprints, and palmprints can be used to tell identical twins apart. Recently, studies carried out in [6], [7], [8], [9], [10], [11] have also proved that facial features and facial recognition systems can be used to tell identical twins apart. However, to the best of our knowledge, no study has yet been 10 carried out in order to analyze the use of facial aging features and asymmetry decomposition features in distinguishing identical twins.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, experiments conducted by Daugman and Downing in 5 [2], by Jain et al in [3], by Srihari et al in [4], and by Kong et al in [5] have shown that biometric identifiers such as the iris, fingerprints, and palmprints can be used to tell identical twins apart. Recently, studies carried out in [6], [7], [8], [9], [10], [11] have also proved that facial features and facial recognition systems can be used to tell identical twins apart. However, to the best of our knowledge, no study has yet been 10 carried out in order to analyze the use of facial aging features and asymmetry decomposition features in distinguishing identical twins.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies carried out in [6], [7], [8], [9], [10], [11] have also proved that facial features and facial recognition systems can be used to tell identical twins apart. However, to the best of our knowledge, no study has yet been 10 carried out in order to analyze the use of facial aging features and asymmetry decomposition features in distinguishing identical twins. It is our aim to extend the study of using facial features to distinguish twins by carrying out comprehensive tests on a large database in order to demonstrate the effectiveness of our proposed approaches and highlight possible areas of improvement in this emerging field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, there are some researchers trying to investigate the familial traits between twins [33,34]. Some of them also analyzed the performance of face recognition between twins [35]. Actually, twins belong to the same family, but their familial traits are more similar than other family members.…”
Section: For Examplementioning
confidence: 99%
“…This step is to nd the stable key points. Then the author referred to the work proposed by Brown and Lowe [35], they used a scheme for tting a 3D quadratic function. This function interpolated the location maximum in local sample points.…”
Section: Keypoint Localizationmentioning
confidence: 99%